Cardiovascular risk in patients with severe mental illness in Italy. Issue 1 (26th October 2020) - Salvi, Virginio; Aguglia, Andrea; Barone-Adesi, Francesco; Bianchi, Davide; Donfrancesco, Chiara; Dragogna, Filippo; Palmieri, Luigi; Serafini, Gianluca; Amore, Mario; Mencacci, Claudio
Abstract: Background: Patients with severe mental illness (SMI), such as schizophrenia or bipolar disorders, are more frequently affected by metabolic syndrome and cardiovascular (CV) diseases than the general population, with a significant reduction in life expectancy. Beyond metabolic syndrome, quantifying the risk of CV morbidity in the long-term may help clinicians to put in place preventive strategies. In this study, we assessed 10-year CV risk in patients with SMI and healthy individuals using an algorithm validated on the Italian general population. Methods: Patients aged 35–69 years diagnosed with SMI were consecutively recruited from psychiatric acute care units. Single CV risk factors were assessed, and 10-year CV risk calculated by means of the CUORE Project 10-year CV risk algorithm, based on the combination of the following risk factors: age, systolic blood pressure, total and high-density lipoprotein cholesterol, diabetes, smoking habit, and hypertensive treatment. Patients' data were compared with those from the general population. The 10-year CV risk was log-transformed, and multivariable linear regression was used to estimate mean ratios, adjusting for age, and education. Results: Three hundred patients and 3, 052 controls were included in the analysis. Among men, the 10-year CV risk score was very similar between patients with SMI and the general population (mean ratio [MR]: 1.02; 95%CI 0.77–1.37), whereas a 39% increase in 10-year CV risk was observed in women with SMI compared to the general population (MR: 1.39; 95%CI 1.16–1.66). Conclusions: In our study, women with SMI were consistently more at risk than the general population counterpart, even at younger age.